PENGARUH KETIDAKPASTIAN LINGKUNGAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL DENGAN KUALITAS SISTEM INFORMASI AKUNTANSI MANAJEMEN SEBAGAI VARIABLE INTERVENING PADA PT. PERKEBUNAN NUSANTARA IV MEDAN - Eka Anggaraini Aritonang; Eka Nurmala Sari; Widia Astuty (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2021)
This exploration plans to inspect and examine the impact of natural vulnerability and hierarchical responsibility on administrative execution by intervening the nature of the executives bookkeeping data frameworks at PT. Nusantara IV Medan Plantation.This exploration was led at PT. Perkebunan Nusantara IV Medan in 2020. This exploration is a quantitative affiliated examination. Legitimacy and dependability tests were completed on 30 respondents with the aftereffects of 4 substantial ecological vulnerability proclamations, 8 legitimate hierarchical responsibility articulations, 11 substantial administration bookkeeping data framework quality explanations and 9 substantial administrative execution questions. The populace and test of this review were 45 administrators of PT. Nusantara IV Medan Plantation. This information assortment method is essential and optional information by breaking down and testing the inward and external models with SEM-PLS investigation.The finishes of the aftereffects of this review are: (1) Environmental Uncertainty positively affects the Quality of Management Accounting Information Systems. (2) Organizational Commitment positively affects the Quality of Management Accounting Information Systems. (3) Environmental Uncertainty positively affects Managerial Performance. (4) Organizational Commitment positively affects Managerial Performance (5) The Quality of Management Accounting Information Systems positively affects Managerial Performance. (6) Environmental vulnerability can positively affect administrative execution on the nature of the board bookkeeping data frameworks. (7) Organizational Commitment Can Have a Positive Effect on Managerial Performance on the Quality of Management Accounting Information Systems